Comparison of outcomes of two intraocular lens implantation procedures for aphakic eyes without capsular support - Zhuo-Ran Liu (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM: To compare the curative effect of retropupillary iris claw intraocular lens(IOL)implantation and posterior chamber ciliary scleral suture fixed IOL in the aphakic eyes without capsular support.METHODS: The present retrospective study included 70 aphakic eyes without capsular support. According to the different surgical methods, the patients were divided into two groups, including group A(35 eyes)with treatment of retropupillary iris claw IOL implantation, group B(35 eyes)with treatment of posterior chamber ciliary scleral suture fixed IOL. The uncorrected visual acuity(UCVA), best corrected visual acuity(BCVA), intraocular pressure(IOP)and corneal endothelial cell density(CECD)of the two groups were documented and compared before operation and 3d, 1, 3, 6mo and 1a after operation. Furthermore, the stability of IOL in both groups, as well as the intraoperative and postoperative complications were recorded.RESULTS: The patients in the present study were followed up for 12 to 14mo. 3d after surgery, UCVA in group A was significantly improved compared with that before surgery(P<0.01), while BCVA had no difference compared with that before surgery(P=0.073).UCVA in group B showed no difference(P=0.097), while BCVA was worse(P=0.002). UCVA and BCVA in both groups were significantly elevated 1mo after surgery(P<0.05), and remained stable 6, 3mo later,respectively. Furthermore, IOP in both groups remained in normal level during the follow up period, 0.7% and 2.3% reduction of CECD in A group and B gruop was observed at 1a after operation respectively(P<0.05). Both IOP and CECD between the two groups have no significant differenc at each time point during the follow up period(P>0.05).There was no significant difference between whole eye astigmatism and corneal astigmatism in A group and B gruop at 1 and 6mo after operation(P>0.05). Additionally, There was 1 case of IOL dislocation in each group after operation, which was further recovered by operation. Significant tilt and deviation of IOL were not observed in the rest of the patients during the follow up period. The other postoperative complications were mild with no difference in complications between the two groups(P>0.05).CONCLUSION: For aphakic eyes without capsular support, both retropupillary iris claw IOL implantation and posterior chamber ciliary scleral suture fixed IOL are safe and effective surgical methods. Retropupillary iris claw IOL implantation has relatively simple operation, lower damage to the eyeball tissue, the shorter operation time, and the quicker recovery of postoperative visual acuity, which is one of the effective clinical treatments.